Scarcity and Survival Horror: Trade as an Instrument of Terror in Pathologic - Novitz, Julian (Transactions of the Digital Games Research Association, 2017)
This paper questions the extent to which the relative scarcity of both gameplay options and in-game resources in survival horror video games can be read as a subversion of the metaphorical and idealised capitalist systems that underpin many forms of gameplay. While survival horror games do tend to offer an alternative to the usual rhythms of work, reward and empowering reinvestment found in many video games, the dystopian absence of common resources, gameplay and features (particularly that of an in-game economy) can just as easily be read as creating a nostalgic longing and appreciation for the norms of more conventional gameplay. Ice-Pick Lodge's Pathologic (2005) is considered as a rare and potentially subversive example of a survival horror game that creates an atmosphere of terror and uncertainty for the player through the fluctuations and predatory movements of its in-game economy, rather than through the absence of this feature.